Partition Anticipation for Wireless Local Area Networks - Butterly, Andrew (Trinity College Dublin. Department of Computer Science, 2002)
Wireless networks introduce new possibilities for computer networking. They also bring some new problems, while enhancing some already established ones. One new problem is a network's increased sensitivity to its environment, while the issues of failure detection, and efficient network routing, are examples of traditional problems that have been exacerbated. The possibility and severity of partition on a network is another problem that has been made worse by the use of wireless solutions. In the case of wireless partitions, there is less scope for predicting a failure than in traditional networks, or judging it correctly as such once it has happened. This is due to the current lack of experience in predicting the characteristics of the wireless medium, as well its inherent unpredictability. This document describes and evaluates solutions for a network location information dissemination protocol, and a framework for a wireless network partition anticipator that uses this location information service. The location service presents a process for relative and absolute user location tracking, network view construction, and routing table construction. The partition anticipator framework analyses the output of the location dissemination service and makes inferences for network quality based on an expert system knowledge base. Potential partitions between nodes, as well as excellent quality connections are highlighted as being interesting.
Keywords: Computer Science